2013
DOI: 10.2166/wst.2013.533
|View full text |Cite
|
Sign up to set email alerts
|

Desalination of oil sands process-affected water and basal depressurization water in Fort McMurray, Alberta, Canada: application of electrodialysis

Abstract: The high content of inorganic species in water used to extract bitumen from the Alberta oil sands and in the groundwater below the oil sands is an increasing environmental concern. These water matrices require treatment before they can be reused or safely discharged. Desalination of the oil sands process-affected water (OSPW) and groundwater, or basal depressurization water (BDW), can be accomplished with deionization techniques such as electrodialysis (ED). In order to achieve the effective ED treatment, OSPW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The exploration of how the fate of the cell can be affected by the substrate properties will contribute to the rational design and therapy strategies based on stem cells. Recent developments in material science, engineering, biotechnology, and biomedical fields have clearly demonstrated the many potential applications of nanotechnology, which can induce a better cellular response than untreated surfaces after cells are placed in contact with these materials. , In our previous study, an increase in the proliferation and an elevation of BrdU incorporation were observed to occur on NPCs cultured on collagen nanofibers, compared with those on collagen-coated surfaces …”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The exploration of how the fate of the cell can be affected by the substrate properties will contribute to the rational design and therapy strategies based on stem cells. Recent developments in material science, engineering, biotechnology, and biomedical fields have clearly demonstrated the many potential applications of nanotechnology, which can induce a better cellular response than untreated surfaces after cells are placed in contact with these materials. , In our previous study, an increase in the proliferation and an elevation of BrdU incorporation were observed to occur on NPCs cultured on collagen nanofibers, compared with those on collagen-coated surfaces …”
Section: Discussionmentioning
confidence: 85%
“…Recent developments in material science, engineering, biotechnology, and biomedical fields have clearly demonstrated the many potential applications of nanotechnology, which can induce a better cellular response than untreated surfaces after cells are placed in contact with these materials. 37,38 In our previous study, an increase in the proliferation and an elevation of BrdU incorporation were observed to occur on NPCs cultured on collagen nanofibers, compared with those on collagen-coated surfaces. 15 Currently, researchers emphasize the effect of scaffolding materials on the function of NSC-derived neurons.…”
Section: Discussionmentioning
confidence: 88%
“…In many industries, for example, seawater desalination, mining, petrochemical, and textile dyeing, high‐salinity wastewater is produced every day. [ 1 , 2 , 3 , 4 , 5 , 6 ] The daily discharge of high‐salinity wastewater from a plant may range from 0.1–10 000 m 3 , depending on the industrial process. [ 7 , 8 , 9 ] Due to the cost and treatment difficulty, these brines are often discharged into aquatic environments without proper treatment, which causes a fatal impact on the aquatic ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Different treatment technologies applied for fluoride elimination have been classified into three categories, namely: adsorption, 10 ion precipitation 11 /co-precipitation 12 and membrane technology. [13][14][15] According to the literature, researchers have studied the phenomenon of fluoride removal using the membrane filtration technique. Pontie et al 14 have studied a phenomenological mass transfer in nanofiltration for a selective defluorination of brackish drinking water in Niakhar, Senegal (Thiès region).…”
Section: Introductionmentioning
confidence: 99%